Effects of moderate-to-high intensity resistance training in patients with chronic heart failure. Issue 17 (1st April 2009) - Spruit, M A; Eterman, R-M A; Hellwig, V A C V; Janssen, P P; Wouters, E F M; Uszko-Lencer, N H M K
Abstract : Context: Resistance training may be beneficial for patients with chronic heart failure (CHF). Objective: To systematically review the methodological quality of, and summarise the effects of, moderate-to-high intensity resistance training in CHF. Data sources: Medline/PubMed, Science Citation Index Expanded, SSCI and A&HCI. Study selection: English language (non-)randomised controlled trials. Data extraction: A predesigned data extraction form was used to obtain data on trial design and relevant results. Methodological quality of the identified trials were scored using the Delphi list. Results: Most of the 10 trials identified had moderate-to-severe methodological limitations. Effects of resistance training (alone or in combination with endurance training) are inconclusive for outcomes like exercise capacity and disease-specific quality of life. Conclusions: Even though moderate-to-high intensity resistance training does not seem be harmful for patients with CHF, the current peer-reviewed evidence seems inadequate to generally recommend incorporation of resistance training into exercise-based rehabilitation programmes for patients with CHF.